Key load indicators and load variability in professional soccer players: a full season study - Oliva-Lozano, J. M.; Barbier, X.; Fortes, V.; Muyor, J. M. (Research in Sports Medicine, 2021)
The aims of this study were to 1) determine the key load indicators in professional soccer through principal component analysis (PCA); and 2) analyse the load variability of each training and match day within the microcycle considering the principal components. Data from 111 load variables were collected using tracking systems in both training and match days (MD). The results showed that 7 variables, which belonged to the first two components of the PCA, explained 80.3% of total variance. Specifically, these variables were Metabolic power, total of steps, Fourier transform (FFT) duration, deceleration distance covered (2-3 m/s2), total of running actions (12-18 km/h; 21-24 km/h), and distance covered (6-12 km/h). Regarding the analysis of the load variability of each training and match day within the microcycle, the lowest load variability was observed in -1MD. Also, a great load variability in +1MD with significant differences compared to -5MD (p<0.001; d=0.49) and -4MD (p=0.01; d=0.26) was found. This study suggests the use of the PCA in the context of team sports to reduce the large number of variables, which are daily managed by strength and conditioning coaches, in addition to the analysis of load variability of each training and match day within the microcycle.